Walory botaniczne śródleśnego stawu w Wilamowie - Woziwoda, Beata (Biuletyn Szadkowski, 2010)
The wetland ecosystems are among the most endangered in Poland. Small water bodies situated within forest complexes are the habitat of many unique species of flora and fauna. They are also an important part of compound hydrological systems in forest ecosystems. The occurrence of more than 90 vascular plant species was noted as a result of research on plants diversity of natural pond (it is about 200 m2 in surface area) with its surroundings, which is located in Wilamów forest complex (the eastern part of Szadek commune). The list of plants includes vulnerable species such as: “Nymphaea alba”, “Drosera rotundifolia”, “Nuphar lutea”, “Ledum palustre” (endangered and protected by the law), “Eriophorum vaginatum” and “E. angustifolium” (locally rare and endangered). This natural site is worthy of preservation and establishment of “Śródleśny staw w Wilamowie” nature protected area is suggested. A stable hydrological regime is the most important for maintenance of biodiversity of this place.